PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK DI PALEMBANG: PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK DI PALEMBANG - Resika, Yeri (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
This research aims to determine the influence of product quality on cosmetic purchasing decisions in Palembang. This type of research is quantitative research which uses research data collection techniques through questionnaires with a Likert scale. This research used 67 respondents. The data analysis method used is linear regression analysis. Based on the results of simple linear regression testing, it shows that the coefficient of determination is 0.627 or 62.7%, this means that product quality can explain purchasing decisions by 62.7% while the remaining 37.3% is explained by other factors not included in this research. The regression coefficient for the product quality variable is 0.687, which has a positive direction, meaning that for every increase in product quality by one point and other variables remaining constant, purchasing decisions will increase by 0.687 units.